1999
DOI: 10.1037/0021-9010.84.5.651
|View full text |Cite
|
Sign up to set email alerts
|

Leakage of relevant information to innocent examinees in the GKT: An attempt to reduce false-positive outcomes by introducing target stimuli.

Abstract: This study focused on the Guilty Knowledge Test (GKT) -a psychophysiological detection method based on a series of multiple-choice questions, each having one relevant and several neutral (control) alternatives. The study examined a new method, designed to reduce false-positive outcomes, due to leakage of relevant items to innocent suspects, by introducing target items (i.e. items known to all examinees, but unrelated to the crime), to which subjects have to respond (e.g., by pressing a key), while answering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
2
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 40 publications
5
56
2
1
Order By: Relevance
“…While a CKT constructed from these materials can successfully indicate whether the unauthorised examinee has viewed privileged information, it may not reveal whether malicious intent was involved. While no existing test can accomplish this, previous research using polygraph measures have shown some success in distinguishing those who are 'guilty' from those who are 'innocent but aware' of crime details when familiarity with actions, rather than knowledge is stressed (BenShakhar, Gronau, & Elaad, 1999;Bradley, MacLaren, & Carle, 1996;Bradley & Warfield, 1984). Although a promising approach, in some cases researchers report a significantly high false-alarm rate for innocent participants who are aware of crime information (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While a CKT constructed from these materials can successfully indicate whether the unauthorised examinee has viewed privileged information, it may not reveal whether malicious intent was involved. While no existing test can accomplish this, previous research using polygraph measures have shown some success in distinguishing those who are 'guilty' from those who are 'innocent but aware' of crime details when familiarity with actions, rather than knowledge is stressed (BenShakhar, Gronau, & Elaad, 1999;Bradley, MacLaren, & Carle, 1996;Bradley & Warfield, 1984). Although a promising approach, in some cases researchers report a significantly high false-alarm rate for innocent participants who are aware of crime information (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on the external validity of the mock-crime paradigm, which has been used extensively in the past 3 decades to evaluate the validity of the GKT (e.g., Ben-Shakhar & Dolev, 1996;Ben-Shakhar et al, 1999;Bradley, MacLaren, & Carle, 1996;Bradley & Rettinger, 1992;Davidson, 1968;Lykken, 1959). We showed that the standard mock-crime procedure, applied in most of these studies, may have weak external validity because it does not tap several factors, which operate in the realistic situation and may reduce memory of some relevant items.…”
Section: Discussionmentioning
confidence: 99%
“…A person (the mannequin), whom you know as Frank, is seated in this room", see Bradley & Warfield, 1984, p. 684). In addition, in many of the mock-crime studies the guilty participants are presented with these details just before the GKT is administered (e.g., Ben-Shakhar, Gronau, & Elaad, 1999), and in some studies, data from participants who could not recall the relevant items in a postexperiment recall test were discarded (e.g., Ben-Shakhar & Gati, 1987). In this study, we manipulated this factor by using the typical mock-crime procedure for half our participants (the standard condition), while using a more realistic procedure for the other participants (the realistic condition).…”
mentioning
confidence: 99%
“…Participants were requested to name the catch number instead of answering 'no'. Inclusion of catch items has been shown to leave detection efficiency in 'guilty' individuals unaffected (Ben-Shakhar, Gronau, & Elaad, 1999).…”
Section: Polygraph Testmentioning
confidence: 99%